1838 Fla. Laws 36 - (:unkn) unknown (My University, 1838)
Ch. 24: Required prospective vendors of dirks, pocket pistols, sword canes, or Bowie knives to pay an annual two-hundred dollar tax. Individuals who wish to carry the previously listed weapons are required to pay a ten dollar tax.
Keywords: TAX - DEALERS